2018
DOI: 10.1038/s41598-018-28165-8
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Head Circumference Growth during the First Year of Life on Early Child Traits

Abstract: Atypical head circumference (HC) growth has been associated with neurodevelopmental disorders. However, whether it is associated with specific aspects of development in early childhood in the general population is unknown. The objective of this study was to assess the predictive value of HC growth as an early biomarker of behavioral traits. We examined longitudinal associations between HC growth from 0 to 12 months and temperament, cognitive, and motor development at 24 months. A subsample of healthy children … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 76 publications
1
31
3
1
Order By: Relevance
“…Length-for-age z score 4.0 <0.001 2.4, 5. in which Nepal was one of the site (Scharf et al, 2018), however, some studies contradict to the consistencies of results associated with head circumference and cognitive development (Martyn et al, 1996;Dupont et al, 2018). We expected head circumference to show a more overall association across domains in the current study, there was, however, a lack of such associations.…”
Section: P-value 95% Confidence Interval Betacontrasting
confidence: 51%
“…Length-for-age z score 4.0 <0.001 2.4, 5. in which Nepal was one of the site (Scharf et al, 2018), however, some studies contradict to the consistencies of results associated with head circumference and cognitive development (Martyn et al, 1996;Dupont et al, 2018). We expected head circumference to show a more overall association across domains in the current study, there was, however, a lack of such associations.…”
Section: P-value 95% Confidence Interval Betacontrasting
confidence: 51%
“…Dupont el al. (47) investigated the predictive value of head circumference during the first year of life on early child development. They demonstrated that post-natal head circumference growth positively predicted gross motor skills as well as behavioral growth at 2 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…The relatively smaller head circumference, albeit within the normal range, in the first months of life with rapid catchup growth by the end of the first year of life may have long-term implications. A recent report documented that the growth of head circumference is a surrogate marker of brain development, and that atypical head circumference growth is associated with neurodevelopmental disorders 43 . Conditions affecting the intrauterine environment were linked to maternal hormonal changes; even mild and transient changes capable of affecting the expression of target genes were reportedly involved in brain growth and maturation 44,45 .…”
Section: Discussionmentioning
confidence: 99%